Ultrasonic Evaluation of Seminiferous Tubules by Frequency Map - Takashima, Y.; Ishikawa, T.; Kobashi, S.; Kuramoto, K.; Hata, Y. (2012 Fifth International Conference on Emerging Trends in Engineering and Technology, 2012)
This paper describes a seminiferous tubules evaluation system using an ultrasonic probe. This system evaluates diameters of seminiferous tubules for azoospermia patients. We employ a 5.0MHz ultrasonic single probe. In the experiment, we employ large and small nylon lines as the healthy and unhealthy seminiferous tubules. We acquired the waveforms by the ultrasonic probe and calculated frequency spectrum by short-time Fourier transform. The system visualizes the position of small and large line by a frequency map. The frequency map shows distance and frequency value. In the results, our proposed method detected the large and small lines. Additionally, the system evaluated distance between probe and these lines clearly. The proposed method thus successfully evaluated the position of the large lines.